Perceived Stress of Mothers, Harsh Discipline, and Early Childhood Mental Health: Insights from a Cross-Sectional Study in Marginalized Roma Communities - Filakovska Bobakova, Daniela; Chovan, Shoshana; Van Laer, Stanislava (International journal of public health, 2024)
Objectives: This study aims to compare the early childhood mental health of children from marginalized Roma communities (MRCs) in Slovakia with that of the majority and explore possible mediating pathways of mothers' perceived stress and harsh discipline practices. Methods: We used data from the first wave of the longitudinal RomaREACH study collected in 2021-2022. Two populations were included in the sample: 94 mother-child dyads from MRCs and 79 from the majority population (children aged 14-18 months). Data were analysed using linear regression, and mediation was tested using PROCESS Macro in SPSS. Results: Belonging to MRCs vs. the majority, perceived stress of mothers and harsh discipline were found to be associated with early mental health problems in children. Perceived stress of mothers partially mediates the relationship between belonging to MRCs vs. majority and harsh discipline and harsh discipline partially mediates the relationship between perceived stress of mothers and the mental health of children. Conclusion: Mothers from MRCs perceive more stress, which is associated with more frequent use of harsh discipline practices having a negative impact on the mental health of young children.
Keywords: Mothers; psychický stres; duševní zdraví; Cross-Sectional Studies; Female; předškolní dítě; Stress, Psychological; Romové; Roma; Humans; ženské pohlaví; rodičovství; matky; lidé; Child, Preschool; Parenting; průřezové studie; Mental Health